Monitoring the Electrochemical Processes in the Lithium–Air Battery by Solid State NMR Spectroscopy - Leskes, Michal (American Chemical Society, 2013)
[Image: see text] A multi-nuclear solid-state NMR approach is employed to investigate the lithium–air battery, to monitor the evolution of the electrochemical products formed during cycling, and to gain insight into processes affecting capacity fading. While lithium peroxide is identified by (17)O solid state NMR (ssNMR) as the predominant product in the first discharge in 1,2-dimethoxyethane (DME) based electrolytes, it reacts with the carbon cathode surface to form carbonate during the charging process. (13)C ssNMR provides evidence for carbonate formation on the surface of the carbon cathode, the carbonate being removed at high charging voltages in the first cycle, but accumulating in later cycles. Small amounts of lithium hydroxide and formate are also detected in discharged cathodes and while the hydroxide formation is reversible, the formate persists and accumulates in the cathode upon further cycling. The results indicate that the rechargeability of the battery is limited by both the electrolyte and the carbon cathode stability. The utility of ssNMR spectroscopy in directly detecting product formation and decomposition within the battery is demonstrated, a necessary step in the assessment of new electrolytes, catalysts, and cathode materials for the development of a viable lithium–oxygen battery.